Tháng Ba 1, 2024

Giá trị của biểu thức \(\sqrt {5 – 2\sqrt 6 } + \sqrt {7 – 4\sqrt 3 } \) là: A \(\sqrt 2 – \sqrt 3 \) B \(2 – \sqrt 2 \) C \(2\sqrt 3 \) D \(2\sqrt 2 \)

Giá trị của biểu thức \(\sqrt {5 – 2\sqrt 6 } + \sqrt {7 – 4\sqrt 3 } \) là:

A \(\sqrt 2 – \sqrt 3 \)

B \(2 – \sqrt 2 \)

C \(2\sqrt 3 \)

D \(2\sqrt 2 \)

Hướng dẫn Chọn đáp án là: B

Phương pháp giải:

Biến đổi \(5 – 2\sqrt 6 = {\left( {\sqrt 2 – \sqrt 3 } \right)^2};\,\,7 – 4\sqrt 3 = {\left( {2 – \sqrt 3 } \right)^2}\)

Áp dụng hằng đẳng thức \(\sqrt {{A^2}} = \left| A \right| = \left\{ \begin{array}{l}A\,\,\,khi\,\,\,A \ge 0\\ – A\,\,\,khi\,\,\,A < 0\end{array} \right..\)

Lời giải chi tiết:

Ta có:

\(5 – 2\sqrt 6 = 2 – 2\sqrt 2 .\sqrt 3 + 3\)\( = {\left( {\sqrt 2 } \right)^2} – 2\sqrt 2 .\sqrt 3 + {\left( {\sqrt 3 } \right)^2}\)\( = {\left( {\sqrt 2 – \sqrt 3 } \right)^2}\)

\(7 – 4\sqrt 3 = 4 – 2.2.\sqrt 3 + 3\)\( = {2^2} – 2.2.\sqrt 3 + {\left( {\sqrt 3 } \right)^2}\)\( = {\left( {2 – \sqrt 3 } \right)^2}\)

\(\begin{array}{l} \Rightarrow \sqrt {5 – 2\sqrt 6 } + \sqrt {7 – 4\sqrt 3 } \\\,\, = \sqrt {{{\left( {\sqrt 2 – \sqrt 3 } \right)}^2}} + \sqrt {{{\left( {2 – \sqrt 3 } \right)}^2}} \\\,\,\, = \left| {\sqrt 2 – \sqrt 3 } \right| + \left| {2 – \sqrt 3 } \right|\\\,\,\, = \sqrt 3 – \sqrt 2 + 2 – \sqrt 3 \,\,\,\,\,\,\,\left( {do\,\,\,\sqrt 2 – \sqrt 3 < 0,\,\,\,2 – \sqrt 3 > 0} \right)\\\,\,\, = 2 – \sqrt 2 \,.\end{array}\)

Chọn B.